No Transits of Proxima Centauri Planets in High-Cadence TESS Data - Gilbert, Emily A.; Barclay, Thomas; Kruse, Ethan; Quintana, Elisa V.; Walkowicz, Lucianne M. (Frontiers in Astronomy and Space Sciences, 2021)
Proxima Centauri is our nearest stellar neighbor and one of the most well-studied stars in the sky. In 2016, a planetary companion was detected through radial velocity measurements. Proxima Centauri b has a minimum mass of 1.3 Earth masses and orbits with a period of 11.2 days at 0.05 AU from its stellar host, and resides within the star's Habitable Zone. While recent work has shown that Proxima Centauri b likely does not transit, given the value of potential atmospheric observations via transmission spectroscopy of the closest possible Habitable Zone planet, we reevaluate the possibility that Proxima Centauri b is a transiting exoplanet using data from the Transiting Exoplanet Survey Satellite (TESS). We use three sectors (Sectors 11, 12, and 38 at 2-minute cadence) of observations from TESS to search for planets. Proxima Centauri is an extremely active M5.5 star, emitting frequent white-light flares; we employ a novel method that includes modeling the stellar activity in our planet search algorithm. We do not detect any planet signals. We injected synthetic transiting planets into the TESS and use this analysis to show that Proxima Centauri b cannot be a transiting exoplanet with a radius larger than 0.4 R$_\oplus$. Moreover, we show that it is unlikely that any Habitable Zone planets larger than Mars transit Proxima Centauri.